Gallbladder adenomyomatosis in an older adult: clinical and histopathological presentation - Alberto Aristides Artiles Garcia; Felipe Jorge Aragón Palmero; Belkis Sonia Cañizares García; Emma Midiannys Griñan Fonte (Gaceta Médica Espirituana)
Background: Vesicular adenomyomatosis is an acquired degenerative disease that is characterized by epithelial proliferation with hypertrophy of the muscular layer and formation of fistulous tracts, known as Rokitansky-Aschoff sinuses. It is considered a benign and rare condition, generally diagnosed after the age of 50, with a higher incidence in women.